Inhibiting ROS-STAT3-dependent autophagy enhanced capsaicin–induced apoptosis in human hepatocellular carcinoma cells. (2nd July 2016) - Chen, Xun; Tan, Miduo; Xie, Zhiqin; Feng, Bin; Zhao, Zhijian; Yang, Kaiqing; Hu, Chen; Liao, Ni; Wang, Taoli; Chen, Dongliang; Xie, Feng; Tang, Caixi
Abstract: Capsaicin, which is the pungent ingredient of red hot chili peppers, has been reported to possess anticancer activity, including that against hepatocellular carcinoma. However, the precise molecular mechanisms by which capsaicin exerts its anticancer effects remain poorly understood. Herein, we have tested the involvement of autophagy in the capsaicin mechanism of action in human hepatocellular carcinoma. HepG2 cancer cells were treated with different doses of capsaicin (50, 100 and 200μmol/L) for 6, 12, and 24 h. Flow cytometry and Caspase-3 activity assay were performed to determine cell apoptosis. Immunofluorescence was performed to visualize LC3-positive puncta. Western blotting was used to detect the expression of the hallmarks of apoptosis and autophagy. Capsaicin can induce apoptosis in HepG2 cells. The expression levels of CL-PARP and Bcl-2 were significantly increased. In line with the apoptosis, capsaicin can trigger autophagy in HepG2 cells. Capsaicin increased LC3-II and beclin-1 expression and GFP-LC3-positive autophagosomes. Pharmacological or genetic inhibition of autophagy further sensitized HepG2 cells to capsaicin-induced apoptosis. Mechanistically, capsaicin upregulated the Stat3 activity which contributed to autophagy. Importantly, we found that capsaicin triggered reactive oxygen species (ROS) generation in hepatoma cells and that the levels of ROS decreased with N-acetyl-cysteine (NAC), a ROS scavenger. Moreover, NAC abrogated the effects of capsaicin on Stat3-dependent autophagy. In this study, we demonstrated that capsaicin increased the phosphorylation of signal transducer and activator of transcription 3 (p-STAT3)-dependent autophagy through the generation of ROS signaling pathways in human hepatoma. Inhibiting autophagy could enhance capsaicin-induced apoptosis in human hepatocellular carcinoma.